Ответ:
5
Пошаговое объяснение:
Дано: [tex]x^{2} + 3x -2 = 0[/tex]
[tex]x_{1}^2 + x_{2}^2 = x_{1}^2 + 2 x_{1} x_{2}+ x_{2}^2 - 2 x_{1} x_{2} = (x_{1} +x_{2})^2 - 2 x_{1} x_{2}[/tex]
За теоремой Виета:
[tex]\left \{ {{x_{1} + x_{1} = -3 \atop {x_{1}x_{2} = -2}} \right.[/tex]
Подставим полученые равенства:
[tex](-3)^2 - (-2 * (-2)) = 9 - 4 = 5[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
5
Пошаговое объяснение:
Дано: [tex]x^{2} + 3x -2 = 0[/tex]
[tex]x_{1}^2 + x_{2}^2 = x_{1}^2 + 2 x_{1} x_{2}+ x_{2}^2 - 2 x_{1} x_{2} = (x_{1} +x_{2})^2 - 2 x_{1} x_{2}[/tex]
За теоремой Виета:
[tex]\left \{ {{x_{1} + x_{1} = -3 \atop {x_{1}x_{2} = -2}} \right.[/tex]
Подставим полученые равенства:
[tex](-3)^2 - (-2 * (-2)) = 9 - 4 = 5[/tex]